Student-centred learning (SCL) in the Malaysian Higher Education Institutions - Nurahimah Mohd. Yusoff,; Abdul Malek Abdul Karim,; Rohana Othman,; Mohaida Mohin,; Siti Azhani Abdull Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Improving the quality of teaching and learning is the second thrust out of the seven strategic thrusts of the National Higher Education Strategic Plan. This second thrust, as outlined by the Ministry of Higher Education, generally aims to produce confident students with a sense of balance and proportion. To realise this national aspiration, holistic programmes that cut across all disciplines and focus on communication and entrepreneurial skills need to be designed. In addition, dynamic and relevant curriculum and pedagogy must be reviewed and enhanced, along with benchmarking both components with leading international institutions. At both school and university levels world-wide, and currently in Malaysia, there has been a call for a move from teacher-centred to student-centred learning. Why? The answer is simply the need to provide students with learning opportunities that promote namely creative and critical thinking, active student engagement, value judgement, and transferable skills i.e. in preparation for the workplace. To date, to the best of authors’ knowledge, no studies have been done to assess the extent of use of SCL in the Malaysian Higher Education Institutions. This study hopes to fill the gap in SCL-related research and suggest a framework to improve the quality of teaching and learning. As such and in line with the Malaysian National Higher Education Action Plan, this study intends to investigate the status of student-centred learning (SCL) in the Malaysian Higher Education Institution (HEI) classrooms. In particular, it looks at the extent of which university instructors practice SCL and its variations in their classrooms. A total of 283 lecturers from both the Malaysian public and private HEIs were sampled randomly. Results of the findings show that a majority of the respondents use Computer assisted learning/ E-learning compared to other SCL approaches such as PBL, collaborative learning, case based learning, and inquiry based learning. Among the seven dimensions of SCL, the study revealed that the highest mean score was for the HOTS dimension with a mean score of 3.03 and the lowest was for the AST dimension with a mean score of 2.56 which falls in the average category. The study also provides suggestions and recommendations in using SCL for Teaching-Learning (T-L). One of the major recommendations is that instructors should take into account the seven dimensions: Learners’ Engagement (LEG); Learners‘ Empowerment (LEP); Collaboration (COL); Teachers’ Role (TRO); Higher Order Thinking Skills (HOTS); Methods/Approaches (APR); and finally, Assessment (AST) when designing the SCL curriculum. They are the main framework as formulated in this study and will enhance the T-L process.